State of the Art in Ethiopian Church Forests and Restoration Options - Kindu, Mengistie; Schneider, Thomas; Wassie, Alemayehu; Lemenih, Mulugeta; Teketay, Demel; Knoke, Thomas (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book, with contributions from leading academics - and including reviews and case studies from Ethiopian Church forests - provides a valuable reference for advanced students and researchers interested in forest and other natural resource management, ecology and ecosystem services as well as restoration options. The book addresses various aspects including a general overview of Ethiopian church forests, the present role and future challenges of church forests. It also discusses their structure and diversity in the context of sustainability and discusses restoration options for surrounding landscapes, under consideration of the circumstances of the land and the needs of surrounding communities. The intended readership includes natural resource professionals in general as well as forestry professionals in particular (practitioners, policymakers, educators and researchers). The book will provide the reader with a good foundation for understanding Ethiopian forest resources and restoration options of degraded landscape.
Part I: General Overview of Ethiopian Church Forests -- 1. Understanding Land Use/Land Cover Dynamics in and the surroundings of Ethiopian Church Forests -- 2. Estimation and mapping of Asabot Monastery Dry Afromontane Forest Carbon Stock Under Diverse Land Use Scenarios -- 3. Land cover changes and forest fragmentation on the surrounding of selected church forests in Ethiopia -- 4. Sacred Texts and Environmental Ethics: Lessons in Sustainability from Ethiopia -- Part II: Present Role and Future Challenges of Ethiopian Church Forests -- 5. The role of Ethiopian Church Forests for Soil Carbon Sequestration -- 6. Aboveground and Belowground Carbon Pools for Some Selected Native and Introduced Tree Species of Abune Teklehayimanot Church Forest, Welayita Sodo, Southern Ethiopia -- Part III: Structure and Diversity of Ethiopian Church Forests -- 7. Floristic Composition, Diversity and Regeneration Status of Woody Plants in Four Church Forests in Ethiopia -- 8. Diversity, Regeneration Status and Socio-Economic Importance of Tara Gedam, Abebaye and Fach Forests, Libokemkem District of South Gondar Administrative Zone, Northwestern Ethiopia -- 9. Woody Vegetation Composition and Structure of Church Forests in Southeast of Lake Tana, Northwest Ethiopia -- 10. Woody Species Composition, Diversity, Structure and Uses of Selected Church Forests in the Central Ethiopia -- Part IV: Restoration Options to the Surrounding Landscapes of Ethiopian Church Forests -- 11. Church Forests as Repositories for Forest Reproductive Material of Native Species and their Possible Role as Starting Points for the Restoration of Degraded Areas -- 12. Ecological Status and Plan for Connectivity of Fragmented Forests as a Means of Degraded Land Restoration in South Gonder, Ethiopia -- 13. Identifying Priority Areas for Conservation in Mojo River Watershed of Ethiopia using GIS-Based Erosion Risk Evaluation -- 14. Ethiopian church forests as monitoring towers in reconstructing climate change and its impacts and to make evidence-based climate-smart restoration efforts -- 15. Rehabilitation sites prioritization on base of remote sensing time series, erosion risk and woody biomass modelling.
Keywords: Geography; Cultural property-Protection.; Historic preservation; Cartography; Geographic information systems; Landscape architecture; Regional Geography; Cultural Resource Management; Conservation and Preservation; Cartography; Geographical Information System; Landscape Architecture